Does hyperglycemia in pregnancy change fetal kidney growth?: a longitudinal prospective study - Neves, Haroldo Millet [UNESP]; Sgarbosa, Fábio [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Vianna, Luana Schneider [UNESP]; Santini, Ana Carolina Monteiro [UNESP]; Sieiro Netto, Lino; Dias, Adriano [UNESP] (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2013)
PURPOSE: To measure fetal renal volume in normoglycemic and hyperglycemic pregnancies. METHODS: A longitudinal prospective study was conducted and included 92 hyperglycemic and 339 normoglycemic pregnant women attended at the prenatal service of a hospital from Rio de Janeiro State. Ultrasound examinations were performed to estimate gestational age at baseline and the kidney volume was estimated using the prolate ellipsoid volume equation. RESULTS: Fetal kidney volume growth between normoglycemic and hyperglycemic pregnancies are significantly different. The fetal kidney volume growth in pregnancy is positively correlated with gestational age explained by these predictor equations, by group: normal renal volume = exp (6.186+0.09×gestational week); hyperglycemic renal volume = exp (6.978+0.071×gestational week) and an excessive growth pattern for hyperglycemic pregnancies may be established according to gestational age. CONCLUSION: This is important for early detection of abnormalities in pregnancy, particularly in diabetic mothers.

OBJETIVO: O estudo foi desenvolvido para medir o volume renal fetal em gestações normoglicêmicas e hiperglicêmicas. MÉTODOS: Estudo prospectivo longitudinal, incluindo 92 gestantes hiperglicêmicas e 339 normoglicêmicas que procuraram o serviço pré-natal de um hospital no estado do Rio de Janeiro. A ultrassonografia foi realizada para estimar idade gestacional e volume renal foi estimado utilizando a equação de volume elipsoide. RESULTADOS: O crescimento fetal e os volumes renais entre gestações normoglicêmicas e hiperglicêmicas são estatisticamente distintos. O aumento do volume renal fetal na gravidez é correlacionada com a idade gestacional, de acordo com as seguintes equações preditores, por grupo: volume renal normal = exp (6,186+0,09×semana de gestação); e volume renal hiperglicêmico = exp (6,978+0,071×semana de gestação). CONCLUSÃO: Estes dados são importantes para detecção precoce de anormalidades na gravidez, principalmente em mães diabéticas.
A hiperglicemia na gravidez altera o crescimento renal fetal?: um estudo prospectivo longitudinal
Keywords: Diabetes; Feto/metabolismo; Hiperglicemia/metabolismo; Complicações na gravidez; Saúde da mulher; Diabetes; Fetus/metabolism; Hyperglycemia/metabolism; Pregnancy complications; Women health